Analisi Tantangan Dan Hambatan Penerapan Kurikulum 2013 Di SD Negeri 060861 - Alda Putriana; Muhammad Fiqri Alwi; Rizki Melinda; Sri Rahmayanti; Safran Safran (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Indonesia has experienced several curriculum changes from 1947 to 2013. These changes are related to how important and strategic the role of the curriculum is in implementing the national teaching system. The 2013 curriculum is an integrated competency and character-based curriculum which is a refinement of the Education Unit Level Curricum (KTSP). The 2013 curriculum places more emphasis on character education, especially at the basic level, which will become the foundation for the next level. This research is descriptive quantitative research which aims to describe or create an objective picture of a situation, starting from data collection and answering the research questions that have been asked. Descriptive quantitative research also aims to obtain broader and deeper information by summarizing various conditions, situations, phenomena, or various variables and circumstances that occurred during the research by presenting what actually happened. The research results show that the obstacles in implementing the 2013 Curriculum come from the government, institutions, teachers and students. This seems to be appropriate that there are several factors that influence implementing the curriculum, namely: support from agencies and school principals, support from fellow teachers, support from students and parents, and support from within the teacher are the main elements. When the elements above encounter obstacles, they will certainly hinder the process of implementing a curriculum.